(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
As digital credentials proliferate across education and workforce systems, questions of trust and usability have become central to their value. Credentials that are not grounded in consistent evidence or aligned to workplace practice provide limited confidence for employers and learners. In practical terms, recognizing skills without observing performance is comparable to certifying swimming ability without seeing someone in the water and understanding the broader context. Swimming in a pool doesn’t mean you can swim effectively in the ocean. This presentation examines the trust challenge facing contemporary skills recognition and Prior Learning Assessment and Recognition (PLAR). While PLAR has long aimed to acknowledge skills gained through work, informal learning, and life experience, its implementation has often been constrained by fragmented evidence sources, labor‑intensive assessment processes, and uneven industry confidence. At the same time, the rapid growth of micro‑credentials and compliance‑driven training has contributed to duplicated learning and limited insight into actual workplace capability. SkillsAware is presented as a practical response that strengthens PLAR by enabling consistent, scalable skills recognition supported by artificial intelligence and industry‑aligned data. Rather than treating skills as abstract or universally transferable, SkillsAware recognizes that capability is contextual. Skills are defined and assessed within specific industry and task settings, reflecting how these tasks are performed. For example, communication in healthcare, construction, and hospitality involves distinct behaviors, risks, and standards that must be recognized explicitly. The platform applies artificial intelligence to analyze skills evidence drawn from multiple sources, including training records, assessments, and workplace observations and measures them against standards or frameworks. Importantly, all metadata standards are open, enabling integration with existing systems. Instead of binary outcomes, SkillsAware uses a probability‑based model to express confidence in skill attribution, based on the breadth and consistency of available evidence. This approach supports more defensible PLAR decisions while reducing the burden on the ultimate decider, the assessor, and improving transparency for employers. Industry collaboration is a critical foundation of trust. Over the past decade, members of the SkillsAware team have co‑developed competency datasets with industry partners across Australia, Asia, and Latin America. This ongoing collaboration ensures that recognized skills remain relevant, current, and aligned to real work expectations, supporting confidence across sectors. SkillsAware enables organizations to move beyond generic credentials toward targeted workforce development. Outcomes include reduced duplication of training, improved hiring decisions, clearer skills visibility, and more effective upskilling strategies. The presentation concludes by outlining a practical vision for an interoperable skills ecosystem in which PLAR, digital credentials, and industry‑grounded data work together. Such systems support workforce mobility, productivity, and lifelong learning by ensuring that skills recognition is consistent, transparent, and trusted by those who rely on it. Keywords: PLAR, skills recognition, digital credentials, AI-assisted assessment, industry-aligned competencies